1970
DOI: 10.1002/1097-0142(197006)25:6<1384::aid-cncr2820250617>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in childhood rhabdomyosarcoma

Abstract: Survival data on 78 children with rhabdomyosarcoma indicated that age, histology, primary site, extent of disease, and treatment each had a significant influence on prognosis. The best survival occurred in patients with sarcoma botryoides, the poorest with alveolar rhabdomyosarcoma, and the intermediate with embryonal rhabdomyosarcoma. Tumors of the orbit had the best prognosis and tumors of other structures of the head and neck had the worst prognosis. Children under 7 years of age had better survival curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
8

Year Published

1972
1972
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(52 citation statements)
references
References 2 publications
0
44
0
8
Order By: Relevance
“…Historically, surgery alone achieved a cure in >20% of patients with RMS, implying that microscopic residual tumor invariably remained or had disseminated in the majority of patients despite a total gross resection [26]. Survival has improved considerably, largely due to cooperative group trials (IRSG) employing multidisciplinary treatment protocols, which include multiagent chemotherapy and radiotherapy in addition to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, surgery alone achieved a cure in >20% of patients with RMS, implying that microscopic residual tumor invariably remained or had disseminated in the majority of patients despite a total gross resection [26]. Survival has improved considerably, largely due to cooperative group trials (IRSG) employing multidisciplinary treatment protocols, which include multiagent chemotherapy and radiotherapy in addition to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Sutow and co-workers found that six of the 14 cases in their study had recurrence or metastatic spread within the first year after diagnosis. [12] However, recurrence following treatment of rhabdomyosarcoma as late as six years has also been reported. [3] Hence the need for long term follow-up of these patients treated for orbital rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Factors affecting the prognosis of rhabdomyosarcoma in children are age, histology, primary site, extent of disease and treatment (Sutow et al, 1970;Proops et al 1984). Patients who present when aged under 2 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyosarcoma has been classified into four pathological categories embryonal, alveolar, pleomorphic and mixed (Horn and Enterline, 1958). Best survival rates are seen in sarcoma botryoids and poorest among children with alveolar rhabdomyosarcoma (Sutow et al, 1970). The anatomy of primary site affects both the timing of the onset of symptoms and opportunities for metastasis (Proops et al, 1984).…”
Section: Discussionmentioning
confidence: 99%